Learn Python in 3 hours - Lai, Rudy (Packt, 2018)
"You are a programmer. You already know many languages, but Python isn't one of them. Today, you need to get up-to-speed with Python in a short period of time, but your search has so far come up with disconnected, unrelated tutorials or guides. Learn Python in 3 hours is a fast-paced, action-packed course that maximizes your time; it's designed from the ground up to bring you from zero to hero in the shortest time. The course is based on many years of Python development experience in both large enterprises and nimble startups. In particular, the course's hands-on and practical approach comes from the author's experience in rapidly iterating and shipping products in a startup setting, where responsiveness and speed are key. With Learn Python in 3 hours, you will be up-and-running with Python like you are with your other languages, proving your value and expertise to your team today, and building your CV and skill set for tomorrow."--Resource description page